Size comparison of quadrats in sample of non-native bivalve Corbicula fluminea (Müller, 1774) (Bivalvia: Corbiculidae) - Paschoal, Lucas R. P. (2013)
We aimed to designate which is the best quadrat area to be used in sampling of C. fluminea for determination of their population parameters. The quadrat of 0.0625 m2 showed the best cost efficiency and a lowest sampling effort, being recommended for study of C. fluminea in lentic environments.